2007
DOI: 10.1007/s00464-006-9148-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic-assisted peritoneal dialysis catheter placement: a microinvasive technique

Abstract: LAPD catheter placement is an easy technique with acceptable catheter longevity and minimal morbidity. The microinvasive technique leads to better patient satisfaction and cosmetic outcome without affecting its function. Therefore, we believe that by promoting microinvasive LAPD catheter placement, PD will gain more acceptance among doctors and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…2,4 Investigators have developed different techniques to minimize the risk of outfl ow obstruction and solve problems such as omentopexy. [5][6][7][8][9] We recently devised a twoport technique for PDC placement with lower abdominal wall fi xation to prevent catheter tip migration.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Investigators have developed different techniques to minimize the risk of outfl ow obstruction and solve problems such as omentopexy. [5][6][7][8][9] We recently devised a twoport technique for PDC placement with lower abdominal wall fi xation to prevent catheter tip migration.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, planned a study combining these techniques, omental wrapping and catheter tip migration, which cause disturbances in fluid inflow or outflow which can be minimized, to make a more clear statement about this method. We observed no significance with having compared to the literature as to the patient mortality and morbidity [6, 7, 1117, 2023]. Laparoscopy also permits to remedial operations such as repositioning of the catheter or dissolving the omental wrapping.…”
Section: Discussionmentioning
confidence: 66%
“…Carrillo et al reported a method using two trocars without accompanying catheter management; their study showed good catheter outcome in a small patient group during a short follow-up period (median follow-up period ¼ 1 year). 13 Laparoscopic PD catheter placement also allows for concomitant procedures during the operation. Adhesiolysis was the most commonly reported combined procedure in several series.…”
Section: Discussionmentioning
confidence: 99%